Pengaruh Substitusi Serbuk Batu Menyan Terhadap Parameter Kuat Geser Tanah Ekspansif - Marshella Pratiwi; Indra Chusaini San (Jurnal Teknik Sipil dan Lingkungan, 2013)
Soil often caused a lot of problem if the soil has a bad attribute, like expansive soil. Expansive soil has a feature to expand and shrink with a high sweeling. Theres a lot of ways to improve the quality of soil, one of them with addition of a chemical substance. To solve the problem of expansive soil, a research need to be done with menyan stone to be the stabilizer, the aim is to find the influence of the substitution of menyan for expansive soil with the soil shear strength, among cohesion value and shear angle of friction value. The result of the research shows that the substitution of menyan stone has anÂ  impact ofÂ  the cohesion and shear angle of friction value. The value increases up to 25% in mix compotition with 21 days treatment. This explains that the menyan stone worthed to be a stabilizer material.Keyword : expansive soil, menyan stone, cohesion, shear angle of friction value.